Employability Skills of Management Graduates: The Comparative Status of SC/ST Students in Andhra Pradesh - Pradeep Kumar, D.; Subbarayudu, Y.; Nagaraju, E. (Prabandhan: Indian Journal of Management, 2019)
The current research was concerned with the employability skills of SC/ST students in comparison with other students of various colleges in Andhra Pradesh. For the purpose, 200 MBA students were selected as sample by using multistage random sampling and data were collected with the help of a structured questionnaire. The statistical techniques, that is, descriptive statistics and independent sample t-test were carried out for the analysis, and interpretation of the data were done through SPSS package. The study revealed that SC/ST management graduates were way behind the other students in almost all employability skill components such as personal qualities, communication skills, team leading, technical skills, higher-order thinking, planning and time management, and analytical skills. It was proposed that the departments and the ministry exclusively meant for providing training to the SC/ST students should function actively. The governments should monitor the activities, budget spending, and the progress of the SC/ST students periodically to address this issue.